Nuclear DNA content in 20 species of Siluriformes (Teleostei: Ostariophysi) from the Neotropical region - Fenerich, Paulo César [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Sociedade Brasileira de Genética, 2004)
In the present study, 20 species of Siluriformes fish were analyzed in order to determine their nuclear DNA content and compare these data with their diploid number. In addition, the extension and importance of the changes that occurred during the process of diversification in the group of Neotropical freshwater catfish were investigated. The only species studied of the family Doradidae, Rhinodoras d'orbignyi (2n = 58), presented 3.46 ± 0.13 pg of DNA. Among the species of the family Heptapteridae, the values of nuclear DNA content and the diploid numbers ranged from 1.13 ± 0.09 pg of DNA in Pimelodella sp. (2n = 46) to 2.38 ± 0.07 pg of DNA in Imparfinis mirini (2n = 58). The family Loricariidae showed the widest variation in diploid number and nuclear DNA content values, ranging from 2n = 52 and 3.96 ± 0.22 pg of DNA in Liposarcus anisitsi to 2n = 76 and 4.90 ± 0.12 pg of DNA in Hypostomus sp. 4. In this group, two local samples of Pimelodus maculatus (Pimelodidae) were analyzed, and both exhibited 2n = 56, but different nuclear DNA content values (2.68 ± 0.22 pg and 2.82 ± 0.20 pg, respectively). Among the Pseudopimelodidae species analyzed, Pseudopimelodus mangurus (2n = 54) showed 2.23 ± 0.15 pg and Microglanis cottoides (2n = 54) exhibited 2.50 ± 0.18 pg of DNA. Two species of Trichomycterus (Trichomycteridae) also presented the same diploid number, 2n = 54 chromosomes, but, while the species from the Quinta stream presented a DNA content of 2.62 ± 0.19 pg, in the sample from the Capivara river this value was 2.30 ± 0.23 pg. In the analyzed species, the results showed that the changes in DNA content were frequently not followed by changes in the diploid number. This fact permits to suggest that, in addition to structural chromosome rearrangements, other mechanisms, including deletions, duplications and polyploidy, could be involved in the process of species differentiation in the representatives of the fish order Siluriformes.
Keywords: nuclear DNA; DNA content; chromosome; fish; evolution